An appreciative dialogue between East and West - Ann Brooks; Qi Sun (Adult Education Research Conference, 2014)
In the context of globalized world, many countries have encountered similar changes and challenges. Learning from one another becomes critical to better understand the strengths and limitations of different theoretical and methodological approaches of education and adult education in particular. International and comparative education have historically demonstrated an effective way of learning from each other. Yet learning from each other seems to become very limited. Instead, learning from the West has become the norm due to its dominant economic position, a legacy of colonialism, the exportation of education, and the development of English as the lingua franca of scholarly publishing and interchange (Altbach, 2008).